Sharing is Good As Always English Literacy and Literature Corner - Putri, Ikmaliza; Lestiny, Wenny (National Conference for Community Service Project (NaCosPro), 2019)
The purpose of this study was to determine the character values ??that can build English learning habits in children who are developing.  The population of this study is all children around Lubuk Baja, which starts from the age of 4 years to 13 years.  A sample of 39 students who took part in the Citizenship learning practice.  This research is a correlative descriptive study so the data are analyzed to find out the relationship between students' English learning habits and student learning outcomes.  Data collection instruments used documentation, games, and direct observation which were then analyzed using question and answer and assessment of arrest of children in answering questions.  The results obtained are character values ??that can build students' English learning habits, namely Honest, Discipline, Responsible, Hard Work, Self-Confidence, and Independent.